1990
DOI: 10.1111/j.1365-2672.1990.tb02889.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, semi‐automated SDS‐PAGE identification system for oral anaerobic bacteria

Abstract: SDS-polyacrylamide gel electrophoresis is a useful technique in bacterial differentiation and identification. A rapid, semi-automated SDS-PAGE system (Phast System) was assessed for identification of formate-fumarate-requiring, asaccharolytic, Gram-negative oral anaerobes. The system permitted loading, separation and staining of gels within 2 h. Percentage similarities between strains were determined using correlation coefficients and cluster analysis. The protein profiles were sufficiently reproducible provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Slayne et al (29) demonstrated the possibilities of the PhastSystem for this technique. We characterized the two morphotypes of P. micros and showed that with this method, it was possible to differentiate between the two morphotypes despite minor differences between strains of one group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slayne et al (29) demonstrated the possibilities of the PhastSystem for this technique. We characterized the two morphotypes of P. micros and showed that with this method, it was possible to differentiate between the two morphotypes despite minor differences between strains of one group.…”
Section: Discussionmentioning
confidence: 99%
“…Before SDS-PAGE the proteins in the supernatant were alkylated as described by Heukeshoven and Dernick (10). The running conditions used for the 12.5% homogeneous acrylamide gel were the conditions described by Slayne et al (29). Low-molecularweight standard proteins were obtained from Pharmacia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eubacterium exiguum is frequently found in periodontitis and periapical infections (Wade, 1997) but is difficult to identify because it is generally unreactive in conventional biochemical tests. In this, it resembles Eubacterium lentum (Moore et al, 1971), an organism found in human faeces, with which it is often confused (Wade et al, 1990). Eubacterium lentum is only rarely reported as being isolated from the mouth when tests capable of distinguishing it from Eubacterium exiguum are performed (Wade et af., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, some species and unnamed taxa provisionally identified as Eubacterium have DNA of high G + C content (Nakazawa & Hoshino, 1994). One such species is Eubacterium exiguum (Poco et al, 1996), formerly designated Eubacterium D6 (Moore et al, 1982(Moore et al, , 1983, Eubacterium S-group (Sato et al, 1993) or Eubacterium Cluster 2 (Wade et al, 1990(Wade et al, , 1994. Eubacterium exiguum is frequently found in periodontitis and periapical infections (Wade, 1997) but is difficult to identify because it is generally unreactive in conventional biochemical tests.…”
Section: Introductionmentioning
confidence: 99%